Auditory localization in helmet wearing and non-helmet wearing conditions - Bharath Raj J; Murthy SS; Chandra P; Natarajan P (Journal of All India Institute of Speech and Hearing, 1970)
Whether auditory localisation ability will he impaired under helmet wearing condition was the focus of study. Localisation functions were studied under helmet wearing and non-helmet wearing conditions. The results pointed out a definite overall impairment under helmet wearing condition and the worst hit directions were Bottom, Back and Top, No appreciable sex differences were observed.